GAMBARAN PENGETAHUAN PERAWAT MENGENAI TRIASE DI UGD RSAU DR. DODY SARDJOTO - Wijayaningsih, Kartika Sari (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The Emergency Room (IGD) is a very important entry point for health services for patients who need urgent treatment and care both urgently and urgently. Triage is a complex decision-making process in order to determine which patients are at risk of death, at risk of disability. , or risk worsening the clinical condition. According to data that researchers obtained from one of the emergency installations of a type B private hospital in the South Sulawesi area which uses the Australian Triage Scale (ATS) triage system, in October – November 2020, there were 1,338 patients who went to the ER for treatment. At this stage, nurses' knowledge about triage and the ability of emergency room nurses plays an important role in reducing the number of disabilities and deaths in the emergency room. Selecting the right patient according to response time and the actions that must be taken will reduce the number of disabilities and deaths in the emergency room. This research aims to analyze and describe nurses' knowledge about triage in the ER RSAU DR. Dody Sardjoto. This research design uses a descriptive design with total sampling. This research was carried out with a questionnaire consisting of 21 questions. The results of this research are the highest category of nurse knowledge in the emergency room at RSAU DR. Dody Sardjoto was in the good category at 71.8%, then at 24% in the good category and finally at 4.2% in the poor category.